Infection of white (at peritoneal macrophages with Toxoplasma gondii (Coccidia: Satcocystidae) after Trypanosoma lewisi(Kinetoplastida: Trypanosomatidae)infection - Catarinella, Gabriela; Chinchilla, Misael; Guerrero, Olga M; Castro, Alfredo (Revista de Biología Tropical, 1999)
Peritoneal macrophages from Wistar rat’s inoculated and non- inoculated with 10 T lewisi trypomastigotes , were cultured and infected with 10 T gondii tachyziodes.